A curriculum model for cybersecurity master's program: A survey of AACSB-accredited business schools in the United States. Issue 8 (17th November 2019) - Yang, Samuel C.
Abstract: There is an increasing recognition of cybersecurity's importance to organizations, and business schools are in a unique position to meet industry's demand for cybersecurity professionals. Using MSIS 2016 and National Centers of Academic Excellence Cyber Defense Education standards, the author investigates cybersecurity master's programs in U.S. business schools. The author surveyed 529 Association to Advance Collegiate Schools of Business–accredited schools and identified 37 cybersecurity master's programs; the five most frequently required courses are information technology security; network security; cybersecurity planning and management; information technology infrastructure; and policy, legal, ethics and compliance. The author also found that the master's programs currently pivot their curriculums toward courses that are cybersecurity and technical in nature. Using survey data, the author develops a new, graduate-level cybersecurity curriculum model for business schools.